Two closely related Homidia species (Entomobryidae, Collembola) revealed by morphological and molecular evidence - Pan, Zhi-Xiang (Zootaxa, 2015)
Two closely related Homidia species, H. fascia Wang & Chen, 2001 and H. pseudofascia sp. nov., are recognized by both morphological and molecular approaches. Both species have minor morphological differences except distinct colour patterns on thorax. Genetic distances (18%) of COI barcodes between them greatly exceed commonly employed threshold (3%), also indicating two independent species. The use of colour pattern in taxonomy of Homidia is also discussed.